Indonesian Mother’ Experiences In Caring For Stunted Children: A Phenomenological Study With Psychosocial Perspective - Giyaningtyas, Ika Juita; Hamid, Achir Yani S. (Alta Dharma Publisher, 2024)
Background: Stunting is a condition that children are too short of normal height in their age range. One of the risk factors for stunting is parenting that is applied in families to children. Mothers are at the core in the stunting phenomenon so that understanding their experiences in caring for the children with stunting is essential. In this study, we explored the Indonesian mothers’ experiences in caring for the children with stunting. Methods: This research was a qualitative research with descriptive phenomenology approach. Using purposive sampling, we recruited 12 mothers who were caring for the children with stunting. Data were collected through in-depth interviews and were analyzed using Colaizzi method. Results: We identified four themes in this study: (1) the diverse responses reflecting the mothers’ subjective burden; (2) negative views from the society adding the burden to the mothers; (3) trying to be at peace with the children’s stunting condition; and (4) the importance of social support in caring for the children with stunting. Conclusion: Mothers caring for children with stunting experienced a multifaceted burdens coupled with the negative stigma from the community. They tried various ways from cognitive and religious approach to passive appraisal to cope with the stressful situation. The mothers also expressed their needs of social support from their husbands, families, and communities to help them through the stressful situation of caring for the children with stunting.